2013
DOI: 10.1007/s13277-013-0986-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of hyaluronic acid binding protein 1 (HABP1)/P32/C1QBP is a novel indicator for lymph node and peritoneal metastasis of epithelial ovarian cancer patients

Abstract: The present study aims to clarify whether hyaluronan binding protein 1 (HABP1/p32/C1QBP) is an indicator of peritoneal and lymph node metastasis in epithelial ovarian cancer (EOC), which to the authors' knowledge is not previously reported by others. Western blot analysis demonstrated that HABP1 was highly overexpressed in most metastatic lesions. Of 89 patients whose primary tumors showed high HABP1 expression on immunohistochemical staining, 85 (95.5%) presented peritoneal metastases and 43 (48.3%) had lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
4
22
0
Order By: Relevance
“…Zhang et al [27] reported that HABP1 mediating pathway was essential for tumor cell metastasis. Furthermore, HABP1 expression levels were observed to gradually increase from primary lesions to metastatic lymph node and peritoneal dissemination lesions among the same epithelial ovarian cancer patients [22]. The above findings further confirmed that HABP1 may play a role in the development of malignancies including TNBC, perhaps acting as an oncogene.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Zhang et al [27] reported that HABP1 mediating pathway was essential for tumor cell metastasis. Furthermore, HABP1 expression levels were observed to gradually increase from primary lesions to metastatic lymph node and peritoneal dissemination lesions among the same epithelial ovarian cancer patients [22]. The above findings further confirmed that HABP1 may play a role in the development of malignancies including TNBC, perhaps acting as an oncogene.…”
Section: Discussionsupporting
confidence: 66%
“…HABP1 played an important role in HA-mediated cellular event, such as cell adhesion and tumor invasion [7], sperm maturity and motility [11], and cellular signaling [7,[12][13][14][15][16][17]. It is reported that HABP1 is differentially expressed in carcinoma [18] and is of clinical significance in cancers, such as epidermal carcinoma [19], breast cancer [20], melanoma [21], ovarian cancer [22], and endometrial cancer [23]. It is suggested that the expression level of HABP1 has been found higher in breast cancer cells with respect to that in normal breast epithelial cells; however, the clinical significance of HABP1 protein expression in TNBCs remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have implicated p32 as a key regulator of cell proliferation, adhesion, migration and invasion, especially in metabolically active and rapidly growing tissues (Feng et al , 2002; Kim et al , 2011). p32 expression is elevated tumours of the breast, epidermis and ovary (Fogal et al , 2008; Chen et al , 2009; Kim et al , 2011; Yu et al , 2013; Zhang et al , 2013), and increased expression correlates with malignancy (Chen et al , 2009; Yu et al , 2013). Association of p32 with the cell membrane has been shown to promote migration and invasion in vitro (Prakash et al , 2011) and may aid tumour cells in evading the complement system by inhibiting the haemolytic activity of C1q (Rozanov et al , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…We incubated sections with primary; rabbit monoclonal antiPro-Ex-C-antibody (MCM2 26H6.19), mouse monoclonal anti-Villin-antibody (clone 1D2C3, ab739 , dilution 1:100) at 4°C overnight (abcam, Cambridge, Ma, USa), antiestrogen receptor (clone gF11, dilution 1:50, Novocastra Laboratories, Newcastle upon tyne, United Kingdom) and anti-progesterone receptor (clone 16, dilution 1:200, Novocastra), followed by incubation with secondary antibodies. Sections from small intestine were used as a positive control for villin, and sections from EMC were used as the positive control for ER and PR receptor expression (20,21). For negative controls, the primary antibodies were removed but replaced with phosphate-buffered saline.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%